1997
DOI: 10.1161/01.cir.95.10.2368
|View full text |Cite
|
Sign up to set email alerts
|

Short-Acting Nifedipine and Diltiazem Do Not Reduce the Incidence of Cardiac Events in Patients With Healed Myocardial Infarction

Abstract: This study showed that use of short-acting nifedipine and diltiazem in this postmyocardial infarction population was associated with a 24% higher cardiac event rate, but this strong adverse trend did not reach statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…[1][2][3] It should also be noted that target patients in the present study had been treated with a sustained-release preparation of nifedipine and the blood concentration curves showed a more gradual concentration gradient than do the curves found with short-acting preparations. The effect on the sympathetic nervous system was therefore relatively subdued, with less increase in heart rate 31 and a reduced burden on the heart.…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3] It should also be noted that target patients in the present study had been treated with a sustained-release preparation of nifedipine and the blood concentration curves showed a more gradual concentration gradient than do the curves found with short-acting preparations. The effect on the sympathetic nervous system was therefore relatively subdued, with less increase in heart rate 31 and a reduced burden on the heart.…”
Section: Discussionmentioning
confidence: 90%
“…The study population, design and method have been reported elsewhere. 11,12) Patient enrollment, study period, and exclusion criteria: Enrollment of this study population was initiated in 1986 and terminated in 1999. Pravastatin became available in 1990 in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects and methods were essentially the same as previously reported. [11][12][13] In the present study, statistical analysis was re-done after adding new cases accumulated up to 2002.…”
Section: Subjectsmentioning
confidence: 99%